Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.langmuir.8b00142
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures in n-Octanol Equilibrated with Additives and/or Water

Abstract: Fluid fatty alcohols are believed to be nanostructured but broadly amorphous (i.e., noncrystalline) fluids and solvents, including the most popular fatty tissue mimetic, hydrated n-octanol (i.e., hydro-octanol). To check this premise, we studied dry octanol and hydro-octanol as a model of relatively short fluid n-alkanols with small-angle X-ray scattering (SAXS). We also combined this alkanol with the matching alkane (i.e., octane) and with a common anti-inflammatory pain killer (ketoprofen). This revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Besides, biphasic solvents as water/alcohol mixtures are known to be nanostructured with a water network embedded in the alkyl chain of the alcohol [42,43]. This allows low water fractions to be achieved, and can modify the reactivity and diffusion of reactive species.…”
Section: Ceoxmentioning
confidence: 99%
“…Besides, biphasic solvents as water/alcohol mixtures are known to be nanostructured with a water network embedded in the alkyl chain of the alcohol [42,43]. This allows low water fractions to be achieved, and can modify the reactivity and diffusion of reactive species.…”
Section: Ceoxmentioning
confidence: 99%
“…Oil-water partition coefficients are commonly reported in conjunction with water solubility and as a measure of a molecule's hydrophobicity, it can also be used to estimate solubility and because of this connection they are often reported together. However, one should be aware that simple determination of separation into octanol and water as is commonly reported may not give a complete general picture of behaviour, particularly when one component has a tendency to associate [26]. Octanol-water coefficients from Staples et al are compared to EPIsuite [18] estimates and calculations by Cousins and Mackay in Fig.…”
Section: Oil-water Partition Coefficientsmentioning
confidence: 99%
“…One of the earliest investigations using X-ray diffraction (or small-angle X-ray scattering, SAXS) revealed the presence of molecular aggregates (clusters) in dry 1-octanol, with estimated aggregation numbers of ≈12; it was suggested that these comprise hydroxyl groups surrounded by extended C 8 hydrocarbon chains, similar to reverse micelles [37]. More recent studies indicate the presence of larger, linear structures [6,38], which Cevc et al [6] have termed "inverse bilayers" occupying "a thermally distorted lattice". As will be seen, this is relevant to the potential role that nanodomains could play in charge conduction in octanol.…”
Section: Evidence For Liquid Nanostructurementioning
confidence: 99%
“…Thus, Figure 1a shows that the dipole moment increases at the highest concentrations [16], which is attributed to an increase in the concentration of associated species, such as chains of octanol molecules (e.g., Figure 1b [39]). Furthermore, it is found that the addition of n-octane to octanol (6:1 octanol:octane, i.e., 87 wt% octanol, equivalent to ≈0.86 mole fraction) results in the formation of a mesophase [6,40], thereby relieving the nanocluster packing stress. Assuming that the same mole ratio is applicable to other alkanes, this would be equivalent to 82 wt% dodecane, which is relevant to the present work.…”
Section: Evidence For Liquid Nanostructurementioning
confidence: 99%
See 1 more Smart Citation